The impact of environmental literacy on the health level of rural residents: evidence from the mountainous areas of Sichuan, China - Yue Shui; Yingjie Yang; Shaoquan Liu (Frontiers in Public Health)
IntroductionEnvironmental pollution and health issues are hot topics of discussion in modern society. However, there is a lack of research from the perspective of subjective factors such as environmental protection to study the impact of environmental literacy on health, especially in rural areas.MethodsFirst, through field research in the mountainous rural areas of Sichuan Province, 396 data points were collected. Based on the KAP model, we constructed an interactive impact mechanism model for the health of rural residents. We used chi-square tests and t-tests to examine the relationship between the background characteristics of rural residents and environmental protection. All environmental literacy variables were classified into strong and weak observational variables, and a multiple linear regression model was employed to explore the impact mechanism of environmental literacy (divided into environmental protection awareness, attitudes, behaviors, and perceptions of environmental pollution) on the health of rural residents.Results and discussion(1) Young village officials with higher education levels are more likely to have stronger environmental literacy. (2) The health status of rural residents is positively affected by their positive attitude towards environmental protection and negatively affected by their environmental protection behaviors. (3) Age, gender, marital status, and party membership have a significant impact on the health of rural residents. The results of this study can enhance the attention to the living environment and health in rural areas, and provide a scientific basis for improving the environmental literacy and health level of rural residents.